A combination of activation and repression by a colinear Hox code controls forelimb-restricted expression of Tbx5 and reveals Hox protein specificity. - Satoko Nishimoto; Carolina Minguillon; Sophie Wood; Malcolm P O Logan (PLoS Genetics)
Tight control over gene expression is essential for precision in embryonic development and acquisition of the regulatory elements responsible is the predominant driver for evolution of new structures. Tbx5 and Tbx4, two genes expressed in forelimb and hindlimb-forming regions respectively, play crucial roles in the initiation of limb outgrowth. Evolution of regulatory elements that activate Tbx5 in rostral LPM was essential for the acquisition of forelimbs in vertebrates. We identified such a regulatory element for Tbx5 and demonstrated Hox genes are essential, direct regulators. While the importance of Hox genes in regulating embryonic development is clear, Hox targets and the ways in which each protein executes its specific function are not known. We reveal how nested Hox expression along the rostro-caudal axis restricts Tbx5 expression to forelimb. We demonstrate that Hoxc9, which is expressed in caudal LPM where Tbx5 is not expressed, can form a repressive complex on the Tbx5 forelimb regulatory element. This repressive capacity is limited to Hox proteins expressed in caudal LPM and carried out by two separate protein domains in Hoxc9. Forelimb-restricted expression of Tbx5 and ultimately forelimb formation is therefore achieved through co-option of two characteristics of Hox genes; their colinear expression along the body axis and the functional specificity of different paralogs. Active complexes can be formed by Hox PG proteins present throughout the rostral-caudal LPM while restriction of Tbx5 expression is achieved by superimposing a dominant repressive (Hoxc9) complex that determines the caudal boundary of Tbx5 expression. Our results reveal the regulatory mechanism that ensures emergence of the forelimbs at the correct position along the body. Acquisition of this regulatory element would have been critical for the evolution of limbs in vertebrates and modulation of the factors we have identified can be molecular drivers of the diversity in limb morphology.